PENGARUH NON TARIFF MEASURES ASEAN TERHADAP ARUS PERDAGANGAN SEKTOR ELEKTRONIKA INDONESIA - N. Fridhowati; A. Asmara (Buletin Ilmiah Litbang Perdagangan, 2013)
Tulisan ini menyajikan gambaran mengenai perdagangan elektronika Indonesia dan menganalisis dampak Non Tariff Measure (NTMs) ASEAN terhadap perdagangan sektor elektronika Indonesia. Studi ini menggunakan pendekatan Inventory dengan menghitung coverage ratio dan pendekatan ekonometrik dengan model cross sectional gravity. Hasil empiris menunjukkan bahwa secara keseluruhan NTMs ASEAN tidak mempengaruhi arus perdagangan elektronika Indonesia. Jika NTMs dikelompokkan menjadi core dan non core measures, ternyata peningkatan core measures akan menurunkan perdagangan sektor elektronika, dan sebaliknya peningkatan non core measures akan meningkatkan perdagangan sektor tersebut. Dengan demikian, kebijakan yang perlu dilakukan oleh pemerintah untuk mengantisipasi meningkatnya penerapan NTMs ASEAN adalah pengembangan industri elektronika dengan mengutamakan kualitas, disain dan inovasi produk. Penyediaan fasilitas uji laboratorium bagi pengujian standar juga perlu diperluas untuk meningkatkan daya saing produk. As tariffs have fallen following the establishment of the General Agreement on Tariffs and Trade (GATT) in 1948, attention has progressively shifted towards non-tariff measures (NTMs). Pervasive NTMs in the ASEAN region will impact on regional trade and make it more difficult for establishing the ASEAN Economic Community by 2015. Electronics sector, which is a potential sector in Indonesia, will be one of the sectors affected by the implementation of NTMs. This article provides a brief of Indonesian electronics trade and implementation of NTMs in ASEAN. It analyzes the impact of ASEAN’s NTMs on Indonesian electronics trade flows. Two approaches are used to estimate the cross sectional gravity model; the inventory approach and the econometric approach. This article shows that the overall ASEAN’s NTMs do not affect Indonesian electronics trade flows. However, if NTMs are disaggregated into core and non-core measures, it finds that an increase in the core measures would reduce Indonesian electronics trade flows, while a rise in the noncore measures would increase the Indonesia electronics trade flows. It recommends that Government should develop electronics industry by focusing on quality, design and product innovation. In addition, to increase Indonesian export competitiveness Government should also provide testing laboratorium with cheaper administration cost.